Combined Pulmonary Involvement in Hereditary Lysozyme Amyloidosis with Associated Pulmonary Sarcoidosis: a Case Report. - McCarthy, Cormac; Deegan, Alexander P; Garvey, John F; McDonnell, Timothy J (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Sarcoidosis is a multisystem inflammatory disorder of unknown cause which can affect any organ system. Autosomal dominant lysozyme amyloidosis is a very rare form of hereditary amyloidosis. The Arg64 variant is extraordinarily rare with each family showing a particular pattern of organ involvement, however while Sicca syndrome, gastrointestinal involvement and renal failure are common, lymph node involvement is very rare. In this case report we describe the first reported case of sarcoidosis in association with hereditary lysozyme amyloidosis.